Fabrication and characterization of a highly temperature sensitive device based on nematic liquid crystal-filled photonic crystal fiber - Wolinski, Tomasz R. (2013)
We report on the fabrication and characterization of a highly sensitive temperature sensor by selectively filling the nematic liquid crystal (NLC) 6CHBT into a single void within the photonic crystal fiber (PCF) structure. The temperature response of the device is experimentally characterized, showing good linearity, repeatability, and sensitivity at around -3.90 nm/°C within the temperature range from 44°C to 53°C. The mode properties of the device are theoretically investigated, confirming the mode coupling principle and the temperature sensitivity of the device.